Fiscal policy in new EU member states : go East, prudent man! - Ondřej Schneider; Jan Zapal (Center for Economic Studies and ifo Institute (CESifo), 2005)
The European Union (EU) accepted ten new member states (NMS) in 2004. These countries, mostly former socialist countries, have had to adjust their economic policies to the EU's standards. Perhaps most difficult has proven to be fiscal policy whereby NMS must comply with the Stability and Growth Pact (SGP) rules. Indeed, six out of the ten NMS have breached the SGP limits and were put in Excessive Deficit Procedure (EDP). While the SGP is being modified, fiscal policy is set to remain on the agenda for all NMS in years to come. In this paper, we analyze fiscal policy in the NMS, focusing primarily on the time period that immediately preceded their EU accession. We analyse the structure and scale of these countries? fiscal policy and identify main trends in revenues and expenditures of their public budgets. We then explore dynamics of fiscal policy in the new member states and isolate main factors of the dynamics. Namely, we show how much of the consolidations was due to the fiscal authorities? effort and how much was caused by external factors. We also show that most NMS governments have run a rather inconsistent fiscal policy and have not consolidated their budgets appropriately by postponing politically difficult consolidation measures. However, we also identify a group of countries characterised by strong reform efforts and responsible fiscal policy-making, supported usually by strong economic growth. In this context, room is given to economic, as well as political economy factors.
Keywords: H87; E62; E6; H6; H2; 330; fiscal policy; new member states; consolidations; Stability and Growth Pact; Excessive Deficit Procedure; growth accounting; probit analysis; Finanzpolitik; EU-Stabilitätspakt; Haushaltskonsolidierung; Wirtschaftswachstum; EU-Erweiterung; EU-Staaten <Osteuropa>